Strengthening the Values of Religious Moderation in the Faculty of Tarbiyah and Teacher Training State Islamic University Kiai Haji Achmad Siddiq Jember - Mukni'ah, Mukni'ah; Rafik, Ainur; Mustajab, Mustajab (Didaktika Religia, 2023)
This article explores the implementation of strengthening the values of tawasuth, tawazun, i'tidal, and tasamuh at the Faculty of Tarbiyah and Teacher Training (FTIK) State Islamic University Kiai Haji Achmad Siddiq (UIN KHAS) Jember. The need for Focus Group Discussion (FGD) for strengthening the values of tawasuth, tawazun, i'tidal, and tasamuh at the FTIK UIN KHAS Jember was also examined. The method used in this research-based community service was qualitative research with Participatory Action Research (PAR) approach. The results of the service show that the Effort to reinforce the values of religious moderation in the FTIK UIN KHAS Jember environment is implemented by organizing workshops that are open to lecturers, education staff, and students. Tawazun values are strengthened by practicing discipline to create balance, time management, and activities as well as developing self-potential through extra and intra-campus activities. The strengthening of i'tidal values is done by making regulations that must be obeyed, UKT financing in accordance with the capacity and ability of students, and continuously strengthening the Ahlus Sunnah Wal Jamah learning environment. Meanwhile, tasamuh values are enhanced by respecting differences of opinion and organizations. The supporting factors in efforts to Strengthen the Value of Religious Moderation at FTIK UIN KHAS Jember are support from the dean, high enthusiasm from students, lecturers, and education staff, teamwork, and the availability of supportive funds. Meanwhile, the inhibiting factor is time constraints due to signal constraints for those who join through online or Zoom meetings.